Colonic stenting: a practical update. Issue 3 (12th March 2013) - Sarkar, Sanchoy; Geraghty, Joe; Rooney, Paul
Abstract : Colonic stenting is part of the UK service provision guidelines for colorectal cancer. However, there are issues about availability and expertise within the UK, and controversies remain regarding various clinical and technical aspects of the technique. Based on the current evidence, this article will provide a practical update on the indications, the clinical and technical considerations and the remaining unanswered questions regarding colonic stenting.